2020
DOI: 10.3389/fpsyg.2020.01502
|View full text |Cite
|
Sign up to set email alerts
|

“Honorable Toward Your Whole Self”: Experiences of the Body in Fatigued Breast Cancer Survivors

Abstract: Introduction: Cancer Related Fatigue (CRF) is one of the most common and detrimental side effects of cancer treatment. Despite its increasing prevalence and severity CRF remains dismissed by the majority of clinicians. One reason for the apparent gap between clinical need and clinical undertaking is the penchant toward reductionist accounts of the disorder: a tendency to discount the interface between the lived experience of sufferers and the multi-dimensional etiology of CRF as it manifests adversely on a day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…Due to oncological treatments, breast cancer survivors have to be aware of inner sensations they have never experienced before, which can affect their body perception [ 36 , 37 ]. This could be helpful to alleviate physical issues [ 38 ]. In line with our results, motives and outcomes related to the need to do physical movements, having time to relax, and body awareness are also relevant as outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to oncological treatments, breast cancer survivors have to be aware of inner sensations they have never experienced before, which can affect their body perception [ 36 , 37 ]. This could be helpful to alleviate physical issues [ 38 ]. In line with our results, motives and outcomes related to the need to do physical movements, having time to relax, and body awareness are also relevant as outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Five focused on African American survivors [46][47][48][49][50], eleven on 'younger' survivors (e.g. under 50 years) [41,43,49,[51][52][53][54][55][56][57][58], nine on return to work [59][60][61][62][63][64][65][66][67], two on cognitive difficulties [68,69], four on lymphoedema [65,[70][71][72], four on cancer-related fatigue [73][74][75][76], five on sexual and/or reproductive health [51,58,[77][78][79], and four on healthy lifestyle factors (i.e. nutrition and exercise) [45,54,80,81].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Previous studies emphasized the role of the body and bodily awareness in patients' experiences with CCRF (Levkovich et al, 2019;Pearce & Richardson, 1996;Penner et al, 2020;Ream & Richardson, 1997). A meta-ethnography, a review based on an interpretative analysis of sixteen qualitative studies showed that embodiment is a central phenomenon in experiencing and responding to CCRF (Bootsma et al, 2020).…”
Section: Introductionmentioning
confidence: 99%